2021
DOI: 10.1007/s10802-021-00856-3
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Relations Between Internalising Problems and ADHD in Childhood: a Symptom Level Perspective

Abstract: ADHD and internalising problems commonly co-occur with up to 50% of children diagnosed with ADHD also suffering from anxiety or depression. However, their developmental relations are currently not well understood. Longitudinal symptom level analyses can provide valuable insights into how difficulties in these areas of psychosocial functioning affect each other. Using Gaussian Graphical Models and Graphical Vector Autoregression Models, this study estimated cross-sectional and longitudinal networks of ADHD and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…Edges between ADHD and GAD were one of the few exceptions and remained more consistent, which may shed light on the positive cross-lags found for internalizing predicting externalizing in the RI-CLPM. Several studies have reported similar associations between internalizing symptoms and ADHD (Biederman et al, 2008;McElroy, Shevlin, et al, 2018;Murray et al, 2022;Speyer et al, 2021;Wichstrøm et al, 2017), though ADHD is usually suggested to increase the probability of anxiety and depression rather than the reverse. Yet, it is possible that after accounting for any stable commonalities between ADHD and GAD (i.e., deficits in executive functioning; Mogg et al, 2015), and ADHD and MDD (i.e., genetic overlap;Riglin et al, 2020), the effect of internalizing on ADHD symptoms is more identifiable at the within-person level during this developmental period (Murray et al, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…Edges between ADHD and GAD were one of the few exceptions and remained more consistent, which may shed light on the positive cross-lags found for internalizing predicting externalizing in the RI-CLPM. Several studies have reported similar associations between internalizing symptoms and ADHD (Biederman et al, 2008;McElroy, Shevlin, et al, 2018;Murray et al, 2022;Speyer et al, 2021;Wichstrøm et al, 2017), though ADHD is usually suggested to increase the probability of anxiety and depression rather than the reverse. Yet, it is possible that after accounting for any stable commonalities between ADHD and GAD (i.e., deficits in executive functioning; Mogg et al, 2015), and ADHD and MDD (i.e., genetic overlap;Riglin et al, 2020), the effect of internalizing on ADHD symptoms is more identifiable at the within-person level during this developmental period (Murray et al, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…Longitudinal investigations of the relations between ADHD and internalising problems have also found support for developmental cascades from ADHD symptoms to internalising problems as well as for cascades in the opposite direction, both in middle to late childhood (Speyer et al, 2021a ) as well as in middle adolescence (Murray et al, 2020a ) and across early childhood to late adolescence (Speyer et al, 2021b ). A number of studies have applied variants of the dual failure model to ADHD-internalising cascades, finding support for mediating effects of peer problems and academic attainment (Powell et al, 2020 ; Roy et al, 2015 ).…”
mentioning
confidence: 99%
“…Indeed, if the latent variable assumption is incorrect, then this may have contributed to the suboptimal fit in some countries. Further, network analysis approaches to mental health can yield valuable information about which particular symptoms may be the highest priority intervention targets owing to their high levels of connectedness to other symptoms (Speyer et al, 2021). Future investigations of cross-cultural differences in the PHQ-9 using network approaches are, therefore, promising for yielding further valuable information about how depressive symptoms may manifest and be captured by psychometric instruments across the world.…”
Section: Discussionmentioning
confidence: 99%